Isolation of Oligotrophic Denitrifiers Carrying Previously Uncharacterized Functional Gene Sequences - Ishii, Satoshi (American Society for Microbiology (ASM), 2011)
Oligotrophic denitrifying bacteria, including those belonging to the genera Herbaspirillum, Azospirillum, and Bradyrhizobium, were obtained using a single-cell isolation technique. The taxonomic composition of the denitrifier population was similar to those assessed by previous culture-independent studies. The sequencing of nitrite reductase and N(2)O reductase genes of these strains revealed previously unknown links between 16S rRNA and the denitrification-functional gene phylogenies. In particular, we identified Bradyrhizobium strains that harbor nirS sequences previously detected only in culture-independent studies.